Fatty acid desaturases modulated octadecanoid pathway in Sesame - Chellamuthu, Muthulakshmi; Sanal, Reshma; Subramanian, Selvi (Journal of Plant Stress Physiology, 2020)
Omega 3 fatty acid desaturases are involved in the production of α-linolenic acid (LNA) an essential omega 3 fatty acid, which is present in only traces in sesame seeds. LNA is the precursor for jasmonic acid which is the end product of octadecanoid pathway. This study was undertaken to analyze the key components of octadecanoid pathway and its relationship with fatty acid content in sesame. Fatty acid desaturation and membrane fluidity are modulated differentially in various stresses. Sesame seedlings were subjected to transient stress to analyse the octadecanoid pathway and its impact on fatty acid desaturation. The mRNA levels of omega 3 desaturases and LNA content were higher in cold stressed sesame seedlings than heat, drought and salinity stresses. The LOX activity and MDA content were higher in heat stressed sesame seedlings. Jasmonic acid content was higher in salinity stressed seedlings while abscisic acid registered the highest in drought stressed seedlings. Chloroplast fatty acid desaturase genes expression was found to increase the LNA content in cold stressed seedlings. The level of membrane damage measured by lipid peroxidation in terms of LOX activity and MDA content were found to be minimal in cold stressed seedling. This suggests a possible role of LNA in membrane fluidity and cold acclimation in sesame. A synergistic role of JA and ABA is also suspected in abiotic stress tolerance in sesame.